Analisis Minat Mahasiswa JPOK Terhadap Cabang Olahraga Catur Di Universitas Jambi - Dea Natasya, Fiska; Junresti Daya, Wawan; Decheline, Grafitte (Dharmas Journal of Sport, 2025)
Research Problems: Chess achievements at the 2023 national student sports week (POMNAS) in South Kalimantan failed to win because the level of student interest in chess last year was not detected. As a result, the selection was not carried out, and only students who had the best achievements in their home regions were dispatched. The purpose of this study was to determine the extent of JPOK students' interest in chess at Jambi University. The approach method used is descriptive quantitative. The research sample consisted of 270 respondents with random sampling techniques. The data analysis used is quantitative descriptive analysis and percentage with the help of Excel. The results showed that the Intrinsic factors of JPOK students' interest in chess were categorized as moderate with a percentage of 46%, the Extrinsic factors of JPOK students' interest in chess were categorized as moderate with a percentage of 58%, and the Intrinsic and Extrinsic factors of JPOK students' interest were categorized as moderate with a percentage of 57%. Intrinsic and Extrinsic factors of JPOK students' interest in chess at Jambi University are categorized as moderate with a percentage of 57%. Through this research, lecturers can understand student interest in chess which is an obstacle that can be anticipated by lecturers as educators. This research is expected that students show more enthusiasm and seriousness in playing chess in order to achieve satisfactory results.